TALK SHOWISU PUBLIK DI TELEVISI DAN DINAMIKA DEMOKRASI - Udi Rusadi (Jurnal Studi Komunikasi dan Media, 2012)
This article describes the audience responses to the role of television talk show participants and their implications for the dynamics of democracy. The article is written based on a audience survey to the talk  show  Apa  khabar  Indonesia Malam in  TVone.  Survey  is  conducted in the city  of  Banjarmasin, South Kalimantan. The research findings show, guestoften emphaisizing self-interest and group and often  to  give  emotional  statement.  Host  has  demonstrated  its  role  as  a  moderator  as  well  as provocateur, trying to dig up and dvelop the conflict as a commodity of media content. Under these conditions confirmed the view that the public sphere as a pillar of democratic played hard by mass media.  Artikel  ini  menggambarkan  tanggapan  khalayak  terhadap   peran  partisipan  talk  show  televisi  dan implikasinya terhadap dinamika demokrasi. Tulisan didasarkan pada hasil survey tanggapan penonton terhadap  talk  show Apa  khabar  Indonesia  Malam  di  TVone.  Lokasi  survey di  wilayah  kota Banjarmasin, Kalimantan Selatan. Temuan penelitian  menunjukkan, nara sumber  talk showdirespon penonton  sering  menonjolkan  kepentingan  diri  dan  kelompoknya  serta  pernyataannya  sering emosional.  Host telah  menunjukkan  peranannya  sebagai  moderator  sekaligus  provokator,  berusaha menggali  konflik  sebagai  komoditas  isi  media.  Kondisi  tersebut  mengukuhkan  pandangan  bahwa public spheresebagai pilar demokrasi sulit diperankan media massa.